Spin-dependent transport in compacted powders of chromic dioxide CrO₂ with anisotropy of nanoparticle shapes - Dalakova, N.V. (Functional Materials, 2015)
Resistive and magnetoresistive properties of compacted powders consisting of nanosized particles of chromic dioxide CrO₂ with dielectric β-CrOOH shells are studied. Anisotropy of tunnel magnetoresistance which is responsible for by the magnetic field orientation relative to the specimen plane is observed. It is shown that the main contribution to the anisotropy of tunnel magnetoresistance is made by formation of the magnetic texture under powder pressing.